A Divestment Strategy at Getronics, APAC Focus. - Le Galleu, Franck (2010)
In this paper we discuss the Divestment Strategy at Getronics, a subsidiary of the Dutch telecom company KPN, with a focus on Asia Pacific (APAC). Getronics has divested a significant number of its subsidiaries over the past few years. There are various reasons for a company to divest assets: getting rid of a liability, re-directing investments towards more profitable markets, expanding through larger local partners, need for cash etc. Yet it can also be a clearly defined strategy. And at KPN/Getronics, it is. The divestment strategy must be the result of thorough thinking at corporate level, based on a robust framework which considers a well defined set of rules, the right timing and consider the interests of main stakeholders. As used by Getronics, a SWOT analysis is a powerful tool to develop and drive strategies. It can also be used to validate a strategy post decision-making. The divestment strategy at Getronics, which affected all regions of the globe, must primarily fit in the core strategy of the company which is to protect and develop its market leadership in the Benelux and to better service its large international clients through its network of subsidiaries and partners. It implies having a robust international delivery capability in place with global reach. But owning a large number of subsidiaries is not a necessity for as long as Getronics remains credible and keeps its customers satisfied. But the more Getronics relies on partners, the riskier it gets. And a major risk is to be seen as a company that only manages partners. This research also focuses on the APAC region where three major divestments took place in China/Hong Kong, Japan and Australia while two main subsidiaries (Malaysia and Singapore) were retained. The focus on a reduced number of cases allows for a deeper analysis. Divestment decisions are strategic in nature hence carry a very sensitive aspect and are made behind closed doors, at a very high management level, and therefore only communicated at a late stage of the process. To understand the divestment strategy from various angles, a qualitative analysis of data was conducted then analysed so that findings, recommendations and conclusions can be presented. Customers have also a keen interest in Getronics’ divestment strategy, especially if it impacts their own strategic locations. While acknowledging that divestments have so far been conducted successfully, they also voice their concerns over future potential risks.We conclude that the divestment strategy at Getronics has been successful so far yet it has reached its limits. Divesting more entities out of the handful of remaining subsidiaries will negatively impact Getronics branding internationally and reduced further its direct global reach. And this success is only relative as the new partnerships have yet to prove they are durable. The global service delivery model which relies heavily on partners makes a lot of sense but it is also very risky as customers may see Getronics as a company that mainly manages partners. We also conclude on the importance for the company to keep a foothold in strategic locations, as requested by some major customers, suggesting de-facto a limitation to the number of subsidiaries that shall be divested in the future.